Analysis of goals second phase of futsal league 2013 - Gonçalves, Matheus Cassita (2015)
The aim of this study was to determine how the goals were made in the second phase of the Futsal League 2013. We analyzed the technical action tactics, as well as the playing time they occurred. The sample consisted of all 214 goals in 48 games that took place in the second phase of the League. Data collection was done through video games, seen on cable TV channels Sportv and ESPN Brazil, the Youtube site and through overviews of the games on the website of the League, these were recorded in Excel 2007 spreadsheets. In the results it is clear that the goal average of the second phase was 4.45 goals per game. Shares technical tactics that stood out from the other were the counterattacks with 40.10%, and 29.46% with positional attack. The set pieces and use the goal line gave added a total of 30.44 %. With respect to game time, it was noted that in the second half of play the incidence of goals is much higher compared to the first time, it was also seen that in the last 10 is when we have the most goals especially through counter - attack and played with the goalie line. This study serves as a reference to assist in the structure and methodologies of coaching. However I believe that further research is needed on the futsal and their goals, particularly on the effectiveness of online game keeper, to see if this time the game who takes advantage of the team is attacking or defending team.